A near-isogenic line for spikelet number in rice with a genetic background of IR64 under various fertilizer conditions. (2nd October 2022) - Sasaki, Kazuhiro; Obara, Mitsuhiro
ABSTRACT: The total spikelet number (TSN) per panicle is an essential factor involved in grain yield among yield components in rice. IR64-NIL12 carrying qTSN12.2- YP4, which was detected on chromosome 12 for TSN per panicle, has been developed in a previous study. It is important to characterize the environment of gene function to increase yields. Thus, we attempted to evaluate IR64-NIL12 grown under no, low, and high fertilizer conditions in 2019 and 2020. Grain yields of IR64-NIL12 were significantly higher than that of IR64 in all conditions. The average grain yield of each condition for IR64 and IR64-NIL12 ranged from 387 to 616 g m −2 . Therefore, qTSN12.2 -YP4 would have an increasing effect on grain yield within this range. The ratio of fertility improved in IR64-NIL12. This rice line exhibited modified traits, such as tiller number and plant height (during the vegetative stage), as well as panicle number (at maturity), which may confer an advantage in terms of light-intercepting characteristics. We also focused on the number of unproductive tillers and dry weight per tiller at the heading stage to investigate the mechanism of the increasing effect of qTSN12.2- YP4 on TSN per panicle. There is a significant difference in dry weight per tiller at heading between IR64 and IR64-NIL12, but not in the percentage of unproductive tillers. Therefore, this result indicated that qTSN12.2- YP4 contributes to increasing dry weight per tiller until the heading stage and, consequently, TSN per panicle. Graphical abstract: uf0001